(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The purpose of this paper is to give an overallassessment of Recruitment &Selection practices in automobile industry, (An Empirical study with specialreference to gender issues). The Automobile industry in India is todaycaught in a vortex of rapid ramp-up of production, sales, lean manufacturingand cost-cutting initiatives coupled with an unusual restlessness and churn inhuman assets. It is passing through a critical phase of increasing complexitiesand quantum changes. Further, the need to align with global best practices,while managing strategic priorities and uncertain government policies requiresa realignment of talent matrices.